Pre-sentence reports and individualised justice: consistency, temporality and contingency - Carr, N.; Maguire, N. (Probation Service, 2017)
This paper reports on selected findings from a study on pre-sentence reports (PSRs) in the Republic of Ireland, entitled Individualising Justice: Pre-Sentence Reports in the Republic of Ireland (Maguire and Carr, 2017). The research was commissioned by the Probation Service and was a small-scale, in-depth study exploring the role of PSRs in sentencing, with a particular emphasis on understanding the process of communication involved from the perspectives of Probation Officers who create the reports and judges who request and receive them. This paper draws on the findings from the research to explore specific aspects of the use of PSRs. It begins by highlighting certain features of the Irish context and then provides a brief overview of the methodological approach before presenting a summary of selected findings, including those relating to the purpose of reports and variation in their use. We explore some of the key themes arising from the research, including consistency, temporality and contingency. We conclude by noting the potential positives of pausing a process, but highlight the need for greater consistency to ensure equitable access across the country.